“You May Not Appreciate This Now, But You May Later”: A Qualitative Analysis of the Impact and Meaning of Legacy Interventions as Defined by Bereaved Parents - Stephanie Barta; Cassandra Matz; Stephany Griswold; Foster Rosemund; Caroline Boyd; Sarah Scott; Eileen Auer Bennett; Jennifer Staab (Patient Experience Journal)
The death of a child is a significant event that affects the family system. Families of dying children need comprehensive support to help them cope with their trauma and loss. However, there is little research that examines parental preferences and grieving support needs. This study explored bereaved parent mentors' perspectives on legacy interventions to identify preferences and guide best practices for legacy interventions provided by pediatric staff. Legacy interventions can be defined as a practice that encourages families to process, create, and reflect on their experiences, stories, and memories. Six parents whose child died ≥2 years ago and who volunteered as parent mentors at a USA children's hospital's parent mentor program participated in focus groups. Participants were asked open-ended questions related to the patient/family's experience at end of life, including legacy intervention provisions. Focus groups were video recorded, transcribed, and analyzed using thematic analysis. Similar ideas and categories were grouped to generate preliminary categories for coding. Codes were analyzed to identify central themes. Data analysis yielded three themes: 1) Types and Functions of Legacy Items/Activities, 2) Meaningfulness of Legacy Items/Activities, and 3) Process of Providing Legacy Items/Activities. Legacy interventions were reported as meaningful to participants because they connect them to their child, the treating hospital, and other bereaved families. To improve care for families whose child has a serious/terminal illness, professionals should be cognizant of the family's perception of legacy interventions and collaborate with the family's most trusted staff to help discuss and provide legacy interventions.